Development of a H2-permeable Pd60Cu40-based composite membrane using a reverse build-up method. (22nd October 2021) - Shinoda, Yasunari; Takeuchi, Masakazu; Dezawa, Norikazu; Komo, Yasuhiro; Harada, Takuya; Takasu, Hiroki; Kato, Yukitaka
Abstract: A new reverse build-up method is developed to fabricate an economical H2 -permeable composite membrane. Sputtering and electroplating are used for the formation of a membrane comprised of a 3.7-μm-thick Pd60 Cu40 (wt.%) alloy layer and a 13-μm-thick porous Ni support layer, respectively. The H2 -permeation measurements are performed under the flow of a gaseous mixture of H2 and He at 300–320 °C and 50–100 kPa of H2 partial pressure. The H2 /He selectivity values exceed 300. The activation energy at 300–320 °C is 10.9 kJ mol −1 . The H2 permeability of the membrane is 1.25 × 10 −8  mol m −1  s −1 Pa −0.5 at 320 °C after 448 h. The estimated Pd cost of the proposed membrane is approximately 1/8 of the cost for a pure Pd60 Cu40 membrane. This study demonstrates that the proposed method allows the facile production of low-cost, Pd-based membranes for H2 separation. Highlights: The porous Ni support layer was formed by electroplating. The membrane has a two-layered structure comprising a Pd60 Cu40 alloy and porous Ni support. The composite membrane has a higher cost-benefit than the rolled membrane. This method is promising for further thinning the membrane and reducing cost.